Conductive hydrogel material containing conductive polymer with MOF structure and preparation method of conductive hydrogel material

By introducing MOF structure and hydrophobic monomer into the conductive hydrogel, a composite material with self-healing and conductive stability is formed, which solves the problems of insufficient mechanical strength, conductivity and environmental adaptability of the conductive hydrogel, and provides applicable High-performance materials for flexible electronic devices.

CN119241771APending Publication Date: 2025-01-03SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505883.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing conductive hydrogels have problems such as insufficient mechanical strength and toughness, unstable conductivity and poor environmental adaptability, which limits their wide application in flexible electronic devices and other fields.

Method used

Using the preparation method of conductive polymer containing MOF structure, the natural polysaccharide and metal salt are modified with organic ligands to form porous crystal materials, and the conductive polymer monomer and hydrophobic monomer are introduced to form composite materials through in-situ interface oxidation polymerization. , a conductive hydrogel with self-healing properties and conductive stability is formed.

Benefits of technology

The excellent self-healing performance, mechanical durability and conductive stability of conductive hydrogels are achieved, which enhances its environmental adaptability within a wide temperature range, provides new choice of flexible electronic materials, and promotes the development of flexible electronic technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241771A_ABST
    Figure CN119241771A_ABST
Patent Text Reader

Abstract

The invention discloses a conductive hydrogel material containing a conductive polymer with an MOF structure and a preparation method of the conductive hydrogel material, natural biomass polysaccharide is used as a raw material, boric acid groups are grafted on the raw material through a boric acid modifier, different porous crystal materials are formed with metal salts and organic ligands, and the porous crystal materials and conductive polymer monomers are subjected to in-situ polymerization, so that the conductive hydrogel material with the MOF structure is obtained. A conductive polymer composite material containing an MOF structure is formed as a conductive filler, acrylamide and a hydrophobic monomer are introduced, and the conductive polymer functional conductive hydrogel containing the MOF structure is prepared through a free radical polymerization method. After the mechanical structure of the conductive hydrogel material is damaged, self-healing can be completed in a short time, and stable mechanical properties and electrochemical properties are kept; the preparation process is simple, the functional conductive hydrogel is prepared through a one-pot method, the raw materials are green, pollution-free and degradable, and the functional conductive hydrogel has wide application prospects in the fields of flexible wearable electronic devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, relates to flexible electronic materials, and specifically relates to a conductive hydrogel material containing a MOF structured conductive polymer and a preparation method thereof. Background Art

[0002] Hydrogels are a type of high molecular polymer with a three-dimensional network structure, which has attracted much attention due to its strong water absorption and water retention. This three-dimensional network structure allows hydrogels to absorb and retain a large amount of water while maintaining their shape. Hydrogels usually exhibit good stretchability, ductility, fatigue resistance and biocompatibility, which makes them have broad application prospects in many fields such as biomedical engineering, drug delivery systems, tissue engineering, soft robots, smart materials, etc. By adding conductive components to the network of hydrogels, conductive hydrogels with both conductivity and mechanical flexibility can be obtained. This material shows great potential in flexible electronic devices, sensors, energy storage devices, etc.

[0003] At present, the main performance defects of conductive hydrogels include insufficient mechanical strength and toughness, unstable conductivity and poor environmental adaptability. These defects limit the widespread application of conductive hydrogels. First, traditional conductive hydrogels generally have problems with insufficient mechanical strength and toughness. This is mainly due to the unevenness of the internal structure of the hydrogel, which makes it easy for external forces to concentrate on short chains, and even a very small force can cause the hydrogel to break. In addition, most hydrogels lack an effective energy dissipation mechanism, so that all external forces are concentrated in the hydrogel, resulting in poor strength and toughness. Secondly, the conductivity of conductive hydrogels is also unstable. Most traditional chemically cross-linked hydrogels have the problem of unstable conductivity and are easily affected by environmental humidity. For example, PEDOT conductive hydrogels are easily delaminated from the substrate due to the penetration of interfacial water in a humid environment, resulting in device failure. Finally, the environmental adaptability of conductive hydrogels is poor. The performance of many conductive hydrogels will drop significantly at extreme temperatures and cannot maintain stable performance over a wide temperature range. For example, some conductive hydrogels will lose some or all of their functions in an environment below zero or above 80 degrees.

[0004] Therefore, conductive hydrogels with high flexibility and stable electrical properties still need further research and exploration. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a conductive hydrogel material containing a MOF structured conductive polymer and a preparation method thereof, which has excellent self-healing properties and conductive properties, good mechanical durability, conductive stability and environmental adaptability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a conductive hydrogel material containing a MOF structure conductive polymer comprises the following steps:

[0008] Step 1, dissolving 2 to 20 parts of natural polysaccharide in 60 to 100 parts of deionized water by mass, adding 0.4 to 0.8 parts of boric acid modifier, stirring at 20 to 40° C. for 1 to 2 hours, standing for 1 to 2 hours, centrifuging, washing, and freeze-drying to obtain modified natural polysaccharide;

[0009] Step 2: dissolving the metal salt in deionized water and the organic ligand in methanol or ethanol at a molar ratio of 1:(1-3) between the metal salt and the organic ligand to form a solution A and a solution B with a concentration of 0.1 mol / L; mixing the solution A and the solution B to form a mixed solution C; transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven and reacting it at 100-180° C. for 24 h to 48 h; filtering after the reaction is completed, and washing and drying the solid phase product;

[0010] Step 3: Disperse 2 to 6 parts of the product of step 2 in a solution containing 1 to 8 parts of a conductive polymer monomer, add 0.5 to 4 parts of an oxidant and 0.5 to 2 parts of a stabilizer, and carry out polymerization at room temperature for 8 to 24 hours. After completion, centrifuge, wash, and dry to obtain a conductive filler;

[0011] Step 4: Stir and dissolve 3 to 6 parts of acrylamide and 2 to 6 parts of the modified natural polysaccharide prepared in step 1 at 50 to 60°C, add 2 to 4 parts of hydrophobic monomer, 0.06 to 0.08 parts of cross-linking agent MBA and 2 to 5 parts of the conductive filler prepared in step 3, react at 50 to 60°C for 1 to 3 hours, then add 0.1 to 0.5 parts of initiator dropwise and react at 60 to 70°C for 2 to 3 hours to obtain a conductive polymer functional conductive hydrogel material containing a MOF structure.

[0012] The present invention also has the following technical features:

[0013] Preferably, the natural polysaccharide in step 1 includes any one of pectin, hemicellulose, sodium alginate and guar gum.

[0014] Preferably, the boric acid modifier in step 1 includes any one of 2-aminophenylboronic acid, 3-aminophenylboronic acid, p-nitrophenylboronic acid and p-methoxyphenylboronic acid.

[0015] Preferably, the metal salt in step 2 includes any one of zinc nitrate hexahydrate, zinc chloride and zinc sulfate heptahydrate.

[0016] Preferably, the organic ligand in step 2 includes any one of 2-methylimidazole and terephthalic acid.

[0017] Preferably, the conductive polymer monomer in step three includes any one of pyrrole, thiophene, aniline and phenylene vinylene.

[0018] Preferably, the oxidant comprises any one of ferric chloride, ammonium persulfate and hydrogen peroxide;

[0019] The stabilizer includes any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol and polyvinyl pyrrolidone.

[0020] Preferably, the hydrophobic monomer includes any one of lauryl methacrylate, ethyl acrylate, butyl acrylate and vinyl ethylene ester;

[0021] The initiator includes any one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0022] Preferably, the washing in step 1, step 2 and step 3 is washing with deionized water and ethanol respectively for 3 to 5 times;

[0023] The drying in step 2 and step 3 is performed in a vacuum drying oven at 60-100° C. for 8-12 hours.

[0024] The present invention also protects a conductive hydrogel material containing a conductive polymer with a MOF structure and prepared by the method as described above.

[0025] Compared with the prior art, the present invention has the following technical effects:

[0026] The present invention uses a boric acid modifier to modify natural polysaccharides, introduces a boric acid structure, and the boric acid group reacts with the hydroxyl group on the natural polysaccharide to form a boric acid ester bond. The boric acid ester bond is a polymer material with a dynamic chemical bond that can automatically repair after being damaged; metal salts and organic ligands are used to form different porous crystalline materials, and conductive polymer monomers are introduced into the structure, and then in-situ interfacial oxidation polymerization is adopted to form a conductive polymer composite material containing a metal organic framework (MOF) structure. By compounding MOF with a conductive polymer, the deficiency of MOF in conductivity can be compensated, and the high specific surface area and adjustable pore structure of MOF are used to improve the overall performance of the composite material. As a conductive filler, the composite material has excellent conductivity, stability and porosity;

[0027] In addition, the present invention introduces acrylamide and hydrophobic monomers. Acrylamide has good mechanical strength, high elasticity, high transparency, high chemical stability, and almost no electroosmosis and adsorption. The hydrophobic monomer can enhance the tensile strength and toughness of the hydrogel. The application of acrylamide and hydrophobic monomers in the hydrogel not only improves the mechanical properties of the hydrogel, but also gives it excellent stretchability. A conductive hydrogel material containing a conductive polymer functional with a MOF structure is prepared by a free radical polymerization method. The material exhibits excellent self-healing and conductive properties, which not only overcomes the limitations of traditional hydrogels in practical applications, but also provides a new material choice for the manufacture of flexible electronic devices, and is expected to promote the further development and application of flexible electronic technology.

[0028] The preparation process of the invention is simple, the functional conductive hydrogel is prepared by a one-pot method, and the raw materials are green, pollution-free and degradable. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a physical picture of the self-repairing performance test of Example 1 of the present invention;

[0030] Figure 2 1 is a reaction mechanism diagram of Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0032] Example 1

[0033] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer having a MOF structure, comprising the following steps. The reaction mechanism is as follows: Figure 2 As shown:

[0034] Step 1, dissolving 10 parts of pectin in 70 parts of deionized water by mass, adding 0.4 parts of 2-aminophenylboronic acid, stirring at 30°C for 2 hours, standing for 2 hours, and then centrifuging, and then washing with deionized water and ethanol for 3 times respectively, and then freeze-drying to obtain a modified natural polysaccharide;

[0035] Step 2, dissolving zinc nitrate hexahydrate in deionized water and terephthalic acid in methanol in a molar ratio of 1:1 to form a solution A and a solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 180° C. for 24 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol for 3 times respectively, and then drying it in a vacuum drying oven at 100° C. for 8 hours;

[0036] Step 3: Disperse 2 parts of the product of step 2 in a solution containing 4 parts of pyrrole by mass, add 0.5 parts of ferric chloride and 0.5 parts of sodium dodecyl sulfate, and polymerize at room temperature for 15 hours. After completion, filter and wash the solid with deionized water and ethanol for 3 times respectively, and then dry it in a vacuum drying oven at 100° C. for 8 hours to obtain a conductive filler;

[0037] Step 4: According to the mass ratio, 3 parts of acrylamide and 2 parts of modified natural polysaccharide prepared in step 1 are stirred and dissolved at 50°C, and then 2 parts of ethyl acrylate, 0.06 parts of crosslinking agent MBA and 2 parts of conductive filler prepared in step 3 are added thereto, and the mixture is reacted at 50°C for 1 hour. 0.1 parts of ammonium persulfate are added dropwise, and the mixture is reacted at 60°C for 2 hours to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0038] Example 2

[0039] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer with a MOF structure, comprising the following steps:

[0040] Step 1: Dissolve 12 parts of hemicellulose in 80 parts of deionized water by weight, add 0.5 parts of 3-aminophenylboronic acid, stir for 1 hour at 20°C, let stand for 1 hour, then centrifuge, wash with deionized water and ethanol for 4 times respectively, and then freeze-dry to obtain a modified natural polysaccharide;

[0041] Step 2, dissolving zinc nitrate hexahydrate in deionized water and 2-methylimidazole in methanol in a molar ratio of 1:2 to form a solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 150° C. for 26 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol for 4 times respectively, and then drying it in a vacuum drying oven at 60° C. for 12 hours;

[0042] Step 3: Disperse 3 parts of the product of step 2 in a solution containing 6 parts of thiophene by mass, add 1 part of ferric chloride and 0.8 parts of sodium dodecyl sulfate, and polymerize at room temperature for 8 hours. After completion, filter and wash the solid with deionized water and ethanol for 4 times respectively, and then dry it in a vacuum drying oven at 60°C for 12 hours to obtain a conductive filler;

[0043] Step 4: Dissolve 4 parts of acrylamide and 3 parts of the modified natural polysaccharide prepared in step 1 at 50°C by stirring, and then add 3 parts of lauryl methacrylate and 0.06 parts of crosslinking agent MBA.

[0044] The mixture was reacted with 3 parts of the conductive filler prepared in step 3 at 60° C. for 3 h, 0.2 parts of ammonium persulfate was added dropwise, and the mixture was reacted at 70° C. for 3 h to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0045] Example 3

[0046] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer with a MOF structure, comprising the following steps:

[0047] Step 1: Dissolve 14 parts of sodium alginate in 80 parts of deionized water by mass, add 0.6 parts of p-nitrophenylboric acid, stir for 1.5 hours at 20°C, let stand for 1.5 hours, then centrifuge, wash with deionized water and ethanol for 3 times respectively, and then freeze-dry to obtain a modified natural polysaccharide;

[0048] Step 2, dissolving zinc chloride in deionized water and terephthalic acid in methanol at a molar ratio of 1:3 to form a solution A and a solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 100° C. for 48 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol for 5 times respectively, and then drying it in a vacuum drying oven at 80° C. for 10 hours;

[0049] Step 3: Disperse 4 parts of the product of step 2 in a solution containing 5 parts of aniline by mass, add 0.8 parts of hydrogen peroxide and 1 part of polyvinyl pyrrolidone, and polymerize at room temperature for 24 hours. After completion, filter and wash the solid with deionized water and ethanol for 5 times respectively, and then dry it in a vacuum drying oven at 80° C. for 10 hours to obtain a conductive filler;

[0050] Step 4: According to the mass ratio, 5 parts of acrylamide and 4 parts of the modified natural polysaccharide prepared in step 1 are stirred and dissolved at 55°C, and then 4 parts of butyl acrylate, 0.07 parts of cross-linking agent MBA and 4 parts of the conductive filler prepared in step 3 are added thereto, and the mixture is reacted at 55°C for 2 hours. 0.3 parts of potassium persulfate are added dropwise, and the mixture is reacted at 65°C for 2.5 hours to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0051] Example 4

[0052] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer with a MOF structure, comprising the following steps:

[0053] Step 1, dissolving 16 parts of guar gum in 90 parts of deionized water by mass, adding 0.7 parts of methoxyphenylboric acid, stirring at 30° C. for 2 hours, standing for 2 hours, and then centrifuging, and then washing with deionized water and ethanol for 3 times respectively, and then freeze-drying to obtain a modified natural polysaccharide;

[0054] Step 2, dissolving zinc chloride in deionized water and 2-methylimidazole in ethanol in a molar ratio of 1:1 to form a solution A and a solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 140° C. for 36 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol three times respectively, and then drying it in a vacuum drying oven at 60° C. for 12 hours;

[0055] Step 3: Disperse 5 parts of the product of step 2 in a solution containing 6 parts of pyrrole by mass, add 2 parts of hydrogen peroxide and 2 parts of sodium dodecyl sulfate, and polymerize at room temperature for 12 hours. After completion, filter and wash the solid with deionized water and ethanol for 3 times respectively, and then dry it in a vacuum drying oven at 60°C for 12 hours to obtain a conductive filler;

[0056] Step 4: According to the mass ratio, 5 parts of acrylamide and 5 parts of modified natural polysaccharides prepared in step 1 are stirred and dissolved at 60°C, and then 3 parts of vinyl vinyl ester, 0.06 parts of cross-linking agent MBA and 5 parts of conductive filler prepared in step 3 are added thereto, and the mixture is reacted at 50°C for 1 hour. 0.3 parts of sodium persulfate are added dropwise, and the mixture is reacted at 60°C for 2 hours to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0057] Example 5

[0058] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer with a MOF structure, comprising the following steps:

[0059] Step 1, dissolving 20 parts of pectin in 100 parts of deionized water by mass, adding 0.8 parts of p-methoxyphenylboric acid, stirring at 30° C. for 2 hours, standing for 2 hours, and then centrifuging, and then washing with deionized water and ethanol for 3 times respectively, and then freeze-drying to obtain a modified natural polysaccharide;

[0060] Step 2, dissolving zinc sulfate heptahydrate in deionized water and terephthalic acid in ethanol at a molar ratio of 1:2 to form solution A and solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 160° C. for 48 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol for three times respectively, and then drying it in a vacuum drying oven at 60° C. for 12 hours;

[0061] Step 3: Disperse 6 parts of the product of step 2 in a solution containing 8 parts of phenylene vinylene by weight, add 3 parts of hydrogen peroxide and 2 parts of polyvinyl alcohol, carry out polymerization reaction at room temperature or under heating conditions, filter after completion, wash the solid with deionized water and ethanol three times respectively, and then dry it in a vacuum drying oven at 60° C. for 12 hours to obtain a conductive filler;

[0062] Step 4: According to the mass ratio, 6 parts of acrylamide and 6 parts of modified natural polysaccharides prepared in step 1 are stirred and dissolved at 50°C, and then 4 parts of ethyl acrylate, 0.07 parts of cross-linking agent and 5 parts of conductive filler prepared in step 3 are added thereto, and the mixture is reacted at 50°C for 1 hour. 0.5 parts of ammonium persulfate are added dropwise, and the mixture is reacted at 60°C for 2 hours to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0063] Example 6

[0064] This embodiment provides a method for preparing a conductive hydrogel material containing a conductive polymer with a MOF structure, comprising the following steps:

[0065] Step 1, dissolving 2 parts of guar gum in 60 parts of deionized water by mass, adding 0.5 parts of 2-aminophenylboronic acid, stirring at 30° C. for 2 hours, standing for 2 hours, and then centrifuging, and then washing with deionized water and ethanol for 3 times respectively, and then freeze-drying to obtain a modified natural polysaccharide;

[0066] Step 2, dissolving zinc sulfate heptahydrate in deionized water and 2-methylimidazole in ethanol at a molar ratio of 1:3 to form a solution A and a solution B with a concentration of 0.1 mol / L, mixing solution A and solution B to form a mixed solution C, transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven to react at 160° C. for 48 hours, filtering after the reaction is completed, washing the solid with deionized water and ethanol three times respectively, and then drying it in a vacuum drying oven at 60° C. for 12 hours;

[0067] Step 3: Disperse 3 parts of the product of step 2 in a solution containing 1 part of aniline by mass, add 4 parts of hydrogen peroxide and 1 part of sodium dodecyl sulfate, and polymerize at room temperature for 20 hours. After completion, filter and wash the solid with deionized water and ethanol for 3 times respectively, and then dry it in a vacuum drying oven at 60° C. for 10 hours to obtain a conductive filler;

[0068] Step 4: According to the mass ratio, 6 parts of acrylamide and 3 parts of modified natural polysaccharides prepared in step 1 are stirred and dissolved at 50°C, and then 3 parts of lauryl methacrylate, 0.08 parts of crosslinking agent MBA and 3 parts of conductive filler prepared in step 3 are added thereto, and the mixture is reacted at 50°C for 1 hour. 0.3 parts of ammonium persulfate are added dropwise, and the mixture is reacted at 60°C for 2 hours to obtain a conductive hydrogel material containing a conductive polymer with a MOF structure.

[0069] The performance tests of the conductive hydrogel materials containing the conductive polymers with MOF structures prepared in the above Examples 1-6 were carried out as follows:

[0070] 1. Conductivity test:

[0071] The conductivity of the hydrogel prepared in Examples 1-6 was tested as follows: The conductivity of the material was tested by an electrochemical workstation. The conductive hydrogel was cut into 35 mm × 4 mm × 4 mm samples and fixed and clamped at both ends of the electrode clamp, and the voltage was set to 1.5 V. The conductivity (σ) of the hydrogel sample was calculated as follows:

[0072] σ=d / (R×A)

[0073] d: distance between adjacent electrodes (mm); R: resistance of hydrogel sample (Ω); A: cross-sectional area of ​​hydrogel sample (mm 2 ).

[0074] The test results of electrical conductivity are shown in Table 1.

[0075] Table 1 Conductivity test results

[0076]

[0077] It can be seen from Table 1 that the conductive hydrogel material containing a conductive polymer with a MOF structure according to the present invention has good conductive properties, which indicates that the hydrogel material has good conductive properties and can effectively and accurately transmit electrical signals when applied to strain sensors.

[0078] 2. Self-healing performance test:

[0079] The self-healing properties of the hydrogels prepared in Examples 1-6 were quantitatively characterized, and tensile tests were performed on the hydrogels before and after self-healing. First, a 35mm×4mm×4mm long strip of hydrogel was prepared in a homemade mold, and the hydrogels before and after cutting were subjected to tensile tests. The self-healing efficiency of the hydrogels prepared in Examples 1-6 was calculated using the following formula:

[0080] Self-healing efficiency (%) = H t / H o ×100%

[0081] H o : Undamaged original tensile strength (KPa); H t :Tensile strength after repair (KPa).

[0082] The self-healing efficiency test results are shown in Table 2.

[0083] Table 2 Self-healing efficiency test results

[0084]

[0085] It can be seen from Table 2 that the self-healing performance of the conductive hydrogel material containing a conductive polymer with a MOF structure of the present invention can reach more than 85%, which shows that the conductive hydrogel has good repair performance.

[0086] The actual picture of the self-repair performance test of Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the present invention has good self-repairing performance.

[0087] In summary, the conductive hydrogel material of the conductive polymer containing the MOF structure of the present invention, wherein the natural biomass is modified by a boric acid modifier, a boric acid-based structure is introduced, and its boric acid group reacts with the hydroxyl group on the natural biomass to form a borate ester bond. Different porous crystalline materials are formed using metal salts and organic ligands, and conductive polymer monomers are introduced into their structures, and then in-situ interfacial oxidation polymerization is adopted to form a conductive polymer composite material containing a metal organic framework (MOF) structure as a conductive filler. Secondly, acrylamide and a hydrophobic monomer are introduced, and a functional conductive hydrogel material containing a conductive polymer with a MOF structure is successfully prepared by a free radical polymerization method, which has self-healing ability and excellent stretchability; it is applied to strain sensors, which have the characteristics of high sensitivity, low detection threshold, fast response and mechanical durability, and have broad application prospects in wearable electronic devices, electronic skins, etc.

[0088] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a conductive hydrogel material containing a MOF structure conductive polymer, characterized in that: The following steps are involved: Step 1, dissolving 2 to 20 parts of natural polysaccharide in 60 to 100 parts of deionized water by mass, adding 0.4 to 0.8 parts of boric acid modifier, stirring at 20 to 40° C. for 1 to 2 hours, standing for 1 to 2 hours, centrifuging, washing, and freeze-drying to obtain modified natural polysaccharide; Step 2: dissolving the metal salt in deionized water and the organic ligand in methanol or ethanol at a molar ratio of 1:(1-3) between the metal salt and the organic ligand to form a solution A and a solution B with a concentration of 0.1 mol / L; mixing the solution A and the solution B to form a mixed solution C; transferring the mixed solution C to a Teflon-lined stainless steel autoclave, placing it in an oven and reacting it at 100-180° C. for 24 h to 48 h; filtering after the reaction is completed, and washing and drying the solid phase product; Step 3: Disperse 2 to 6 parts of the product of step 2 in a solution containing 1 to 8 parts of a conductive polymer monomer, add 0.5 to 4 parts of an oxidant and 0.5 to 2 parts of a stabilizer, and carry out polymerization at room temperature for 8 to 24 hours. After completion, centrifuge, wash, and dry to obtain a conductive filler; Step 4: Stir and dissolve 3 to 6 parts of acrylamide and 2 to 6 parts of the modified natural polysaccharide prepared in step 1 at 50 to 60°C, add 2 to 4 parts of hydrophobic monomer, 0.06 to 0.08 parts of cross-linking agent MBA and 2 to 5 parts of the conductive filler prepared in step 3, react at 50 to 60°C for 1 to 3 hours, then add 0.1 to 0.5 parts of initiator dropwise and react at 60 to 70°C for 2 to 3 hours to obtain a conductive polymer functional conductive hydrogel material containing a MOF structure.

2. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The natural polysaccharide described in step 1 includes any one of pectin, hemicellulose, sodium alginate and guar gum.

3. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The boric acid modifier described in step 1 includes any one of 2-aminophenylboronic acid, 3-aminophenylboronic acid, p-nitrophenylboronic acid and p-methoxyphenylboronic acid.

4. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The metal salt in step 2 includes any one of zinc nitrate hexahydrate, zinc chloride and zinc sulfate heptahydrate.

5. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The organic ligand in step 2 includes any one of 2-methylimidazole and terephthalic acid.

6. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The conductive polymer monomer in step three includes any one of pyrrole, thiophene, aniline and phenylene vinylene.

7. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The oxidant includes any one of ferric chloride, ammonium persulfate and hydrogen peroxide; The stabilizer includes any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinyl alcohol and polyvinyl pyrrolidone.

8. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The hydrophobic monomer includes any one of lauryl methacrylate, ethyl acrylate, butyl acrylate and vinyl ethylene ester; The initiator includes any one of ammonium persulfate, potassium persulfate and sodium persulfate.

9. The method for preparing a conductive hydrogel material containing a MOF structure conductive polymer according to claim 1, characterized in that: The washing in step 1, step 2 and step 3 is washing with deionized water and ethanol for 3 to 5 times respectively; The drying in step 2 and step 3 is performed in a vacuum drying oven at 60-100° C. for 8-12 hours.

10. A conductive hydrogel material containing a MOF structured conductive polymer prepared by the method according to any one of claims 1 to 9.